Hematologic Presentations of COVID-19 Can be Misinterpreted as Acute Myeloid Leukemia - Moradi Tabriz, Hedieh; Nazar, Elham; Jazayeri, Fatemeh; Javadi, Arezoo Eftekhar (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: COVID-19 infection prompts inflammatory responses and acute lung injury in human beings. Complete blood count with differential is essential investigative tool in its managing. However, very few studies revealed the variations of blood cell morphology in this disease. Case report: We reported a 39-years- old female patient complained of respiratory distress one week prior to hospitalization. The patient suffered from cough, fever, and molecular test was reported positive for COVID-19 infection. Laboratory data revealed severe permanent leukopenia and peripheral blood smear examination showed blastoid cells after remission of respiratory signs. Patient underwent bone marrow biopsy for rule out acute myeloid leukemia. But, on bone marrow sample, only viral cytopathic effects were seen. COVID-19 virus stimulates inflammatory cells to produces various inflammatory cytokines and as a result, viral cytopathic effects on white blood cells is seen. Conclusion: We have described how the characteristic peripheral blood findings of COVID‐19 infection can be misinterpret as acute myeloid leukemia.